First larvae of Raphidioptera from Eocene Sakhalinian and Rovno ambers - Makarkin, Vladimir N.; Perkovsky, Evgeny E.; Anisyutkin, Leonid N.; Dubovikoff, Dmitry A. (Zootaxa, 2022)
We describe two larvae of Raphidioptera probably belonging to different genera of Raphidiidae, the first recorded from middle Eocene Sakhalinian amber and late Eocene Rovno amber. The Sakhalinian larva is the first confirmed representative of Raphidioptera from the Cenozoic of Asia, and most probably the oldest larvae of an extant family of the order. The Rovno amber larva is the first European Cenozoic immature raphidiopteran found outside of Russo-Scandia. The terrestrial insect assemblage of the Sakhalinian amber forest is discussed, including snakeflies. An abundance of aphids and rarity of ants distinguishes this assemblage from other Cenozoic amber faunas.